Designing and explaining the model of increasing the intention to select tourism destinations through introverted marketing - Mehdi Mohammadi Kuchesfahani; Mohammad jalili; Mahmoud Nouraie (تحقیقات کاربردی علوم جغرافیایی)
Despite Iran's capabilities in the field of tourism, unfortunately, it has not been able to achieve a worthy position in this industry. One of the factors that can develop and improve the country's tourism industry is the use of effective marketing tools and parameters, including introverted marketing. This research is applied in terms of purpose and descriptive-analytical in terms of method. The statistical population of the study consisted of incoming tourists to hotels and restaurants active in the city of Rasht who were active in social networks. The sample size was estimated to be 384 using the Cochran's formula. The data collection tool was a researcher-made questionnaire whose validity was confirmed as qualitative and quantitative validity and its reliability was confirmed using Cronbach's alpha method and combined reliability. In this study, in order to analyze the research data from the software SPSS and Amose were used. The findings of this study showed that the components of social construction, social listening and online content of introverted marketing have a positive and significant effect on the intention of electronic advertising. The results of this study also showed that the components of introverted marketing, ie social construction, social listening and online content have a positive and significant effect on the selection of tourism destinations. Other results of this study can be the positive and significant effect of advertising intentions on the choice of tourism destinations and also the mediating role of this variable in the relationship between the components of introverted marketing with the selection of tourism destinations.